Effects of even- versus uneven-aged tree species (Pinus massoniana and Castanopsis hystrix) mixing on microbial communities across bulk soil, rhizosphere soil, and fine roots - Liu, Runhong; Bai, Yuxin; He, Peng; Cen, Qilan; Luo, Xinyu; Yang, Liurong; Ming, Angang; Shu, Weiwei; Shen, Weijun (Frontiers in Microbiology, 2025)
IntroductionMixed-species plantations are a promising strategy to increase productivity and promote sustainable forest management. However, the effects of even-aged and uneven-aged tree species mixtures on microbial communities along the root–soil continuum remains underexplored.MethodsWe investigated the bacterial and fungal communities across three distinct microhabitats—bulk soil, rhizosphere soil, and fine roots—within two mixed plantations (even- and uneven-aged) and their respective monocultures.ResultsOur results show that while even-aged mixing had no significant impact on microbial alpha diversity across the three microhabitats, uneven-aged mixing significantly altered some specific indices, indicating that uneven-aged mixing has a greater impact on microbial alpha diversity than even-aged mixing. Both mixing modes significantly altered microbial community composition, with mixed plantations exhibiting intermediate characteristics between monocultures. Although microbial taxonomic and functional compositions were largely unaffected by even-aged and uneven-aged mixing in most cases, distinct differences emerged across microhabitats. Notably, mixed plantations showed increased complexity in fungal co-occurrence networks and harbored more bacterial and fungal keystone species. Fungal communities were more sensitive to both mixing modes, whereas bacterial communities were more strongly influenced by soil environmental factors, particularly pH, which emerged as the primary driver of microbial variation across all plantation types.DiscussionOur findings highlight that the effects of tree species mixing on microbial communities vary significantly with mixing mode, microhabitat, and microbial taxa, and these should be emphasized in future research and silvicultural practices.